2021
DOI: 10.1002/hec.4399
|View full text |Cite
|
Sign up to set email alerts
|

Does a health crisis change how we value health?

Abstract: The general population is also impacted, including through increased anxiety and depression (Davillas & Jones, 2020). The economic fallout of the pandemic and its long-term health consequences, including a backlog of demand due to canceled operations, will result in continued pressure on healthcare resources in the future (Leahy et al., 2020). As a consequence, the processes for making decisions about how to allocate scarce healthcare resources will likely become more heavily scrutinized by all stakeholders, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…It is unknown if the pandemic had an impact on how the general population valued health states, in particular whether these utilities are different from pre-COVID utilities and whether they will remain stable for the post-pandemic era. Findings from a recent study comparing EQ-5D-5L health state valuations (by using EQ VAS) before and during the pandemic in the UK suggest that COVID-19 may have affected health preferences among members of the general public [ 16 ]. Nevertheless, findings from EQVAS values may not be generalisable to cTTO utilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unknown if the pandemic had an impact on how the general population valued health states, in particular whether these utilities are different from pre-COVID utilities and whether they will remain stable for the post-pandemic era. Findings from a recent study comparing EQ-5D-5L health state valuations (by using EQ VAS) before and during the pandemic in the UK suggest that COVID-19 may have affected health preferences among members of the general public [ 16 ]. Nevertheless, findings from EQVAS values may not be generalisable to cTTO utilities.…”
Section: Discussionmentioning
confidence: 99%
“…The EQ-5D-Y-3L is a three-level youth measure targeting populations aged 8-15 years [13,14]. However, it requires a separate value set due to the differences in the wording of descriptive system and utilities elicited for children/adolescents in comparison with adults [9,[15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ranking of the domains remained identical with and without the data collected during the pandemic [ 12 ]. However, a dedicated study on the effect of the COVID-19 pandemic on the attributed VAS values [ 27 ] to the best health state (11111), dead and the worst health state (55555, when using the five-level version of the EQ-5D-5L) indicated that the best health state and dead were valued lower, whereas the worst health state was valued higher post-pandemic compared with before the pandemic. Differential effects were also found by age, sex and education on the raw VAS values, and particularly relevant is the age effect on the worst health-state valuation, with older participants receiving higher scores post-pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The respondents assessed the availability of services provided by a primary care physician, specialist care, as well as the costs and quality of treatment of the Polish health care system, as better than the British system. It should be emphasized however, that the study was conducted prior to the SARS COVID-19 epidemic, which undoubtedly had a different effect on Polish and British health care systems, as well as societal responses [16,17]. The following may be considered as potential reasons for the higher assessment of medical services in Poland in relation to the United Kingdom: 1) Higher work culture of doctors in Western countries, which limits the over-exploitation of health care staff, by setting strict limits on the number of patients that can be attended to on a given day.…”
Section: Discussionmentioning
confidence: 99%